Lista de especies de peces de la cuenca del Río Ucayali, Perú - Chuctaya, Junior (2022)
This study presents an updated checklists of the fish species recorded in the Ucayali River basin, Peru, from published and unpublished data. Ucayali River basin shows a rich and diversified ichthyofauna, with 734 species distributed in 15 orders, 49 families and 292 genera. It is composed by miniature fishes (4 %, < 2.6 cm of standard length), small fishes (39 %), medium fishes (41 %), large fishes (13 %) and giants (3 %). The dominant groups are Characiformes (312 species, 43.0 %), Siluriformes (270 species, 36.8 %), Gymnotiformes (51 species, 6.9 %) and Cichliformes (50 species, 6.8 %). Part of the ichthyofauna is shared with the adjacent basins as Marañón and Amazon, mainly in the confluence area, which contribute to the highest diversity of fishes in the Ucayali basin. High diversity of fishes with restricted distribution was observed, among them Orestias, Astroblepus, Trichomycterus, Hemibrycon genera that occur in the headwaters. Estimates of species richness considering their distribution per 100 m of altitude, show that the Ucayali basin is underestimated, expecting to find up to 1125 species. The results presented here are background information that will contribute to decision-making for conservation and sustainable development purposes in the Amazon region.